2010
DOI: 10.1080/00185861003768993
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Leadership: The Rush University Medical Center Experience

Abstract: Meeting the challenges of diversity is crucial, and within healthcare organizations a particularly strong case exists for a diversity strategy. Rush University Medical Center in 2006 was at an important juncture. Since its founding, the organization had made notable progress toward advancing diversity and inclusiveness. On the other hand, many diversity-related problems continued. Rush convened a committee to review the work of the institution in this area. The committee's report called for changes, and a Dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…All studies retrieved were written in English. All included studies were comprised of national audits (n = 6), 22‐27 organisational audits (n = 4), 28‐31 consensus methodology (n = 1), 32 narrative reviews (n = 7), 8,30,33‐37 university audits (n = 3), 34,37,38 project audits (n = 7), 33,37,39‐43 viewpoints (n = 8), 2,3,18,44‐48 simulation experiments (n = 3), 49‐51 case surveys (n = 5) 52‐56 and a position paper (n = 1) 15 . Studies centred on ethnic minorities in the United States of America, 2,3,15,22,24‐28,30‐34,36,37,41‐59 China, 24 Switzerland 60 and United Kingdom 18 ; women who identified as an ethnic minority 25,28,38 ; Indigenous peoples 14,35,40,61 ; both ethnic minorities and Indigenous peoples 2,57 ; and people with low socio‐economic status 23,48 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies retrieved were written in English. All included studies were comprised of national audits (n = 6), 22‐27 organisational audits (n = 4), 28‐31 consensus methodology (n = 1), 32 narrative reviews (n = 7), 8,30,33‐37 university audits (n = 3), 34,37,38 project audits (n = 7), 33,37,39‐43 viewpoints (n = 8), 2,3,18,44‐48 simulation experiments (n = 3), 49‐51 case surveys (n = 5) 52‐56 and a position paper (n = 1) 15 . Studies centred on ethnic minorities in the United States of America, 2,3,15,22,24‐28,30‐34,36,37,41‐59 China, 24 Switzerland 60 and United Kingdom 18 ; women who identified as an ethnic minority 25,28,38 ; Indigenous peoples 14,35,40,61 ; both ethnic minorities and Indigenous peoples 2,57 ; and people with low socio‐economic status 23,48 …”
Section: Resultsmentioning
confidence: 99%
“…‘Old boy networks’ are described as social networking systems and perceptions that reinforce traditional predominantly White/Caucasian power structures through limiting hiring practices or business transactions to ethnic minorities 62 . Many studies showed that mentorship and assistance with skill acquisition prepare candidates for successful surgical training and the potential for academic faculty member and leadership appointments 16,33,34,43 . However, Wong et al 69 showed that African‐American residents were more likely to feel that they could not ask for help from attending physicians or peers, would be punished more harshly for mistakes and felt like they had to work harder and go the extra mile to ensure success.…”
Section: Discussionmentioning
confidence: 99%